Knowledge, attitude and practices of mothers of under five children with ARI at QECH, Blantyre, Malawi. - Suwedi, Leticia Chimwemwe (Kamuzu University of Health Sciences, 2022)
Background: Acute respiratory tract infection (ARI) in under five children has been the major cause of morbidity and mortality since 1960's worldwide, developing countries contributing 70% to the burden. 80% of children suffering from ARI in Malawi are taken late to health facilities. WHO (2002) estimates show that seeking prompt and appropriate care could reduce child deaths due to ARI by 20%.Health education programs can be effective when designed to take account the prevailing knowledge, attitude and practices of mothers of under five children with ARI.